Hibah as alternative to resolve inheritance issue among new Muslim converts (Muallaf) in Malaysia : an analysis - Amylia Fuziana Azmi,; Nik Salida Suhaila Nik Saleh,; Mohamad Zaharuddin Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In Malaysia, Muslim converts (Muallaf) face certain difficulties including restrictions in inheritance. In this regard, Islam provides that the property of Muslims shall be inherited by Muslim heirs only. In other words, the general principle provides that non-Muslim heirs have no right in inheritance to property that belonging to Muslims. By taking into consideration the status and rights of family members of Muallaf in Malaysia, hibah is categorized as an alternative method of distribution, in addition to wasiat and other methods. In recent years, there has been an increasing interest in studying and promoting hibah (inter vivos gift) as one of the alternatives in distributing someone’s wealth, in addition to other methods. This paper applies a doctrinal legal research methodology where data collection involves primary and secondary sources which include Al-Quran, hadith, journal articles, constitution, statutes and case law. This study seeks to identify the extent hibah applies as an alternative to resolve the inheritance issue among the Muallaf and to provide some recommendations in proposing hibah law to be enacted in resolving this issue in Malaysia. To date, none of the authors has studied in detail drafting of hibah law to be enacted for resolving the inheritance issue concerning Muallaf in this country. This study discovers that a specific law on hibah could clarify its position and application in Malaysia where it can further be used as an alternative to resolve inheritance conflict affecting the heirs, especially non-Muslim, of Muallaf. Furthermore, it may also benefit various agencies such as religious departments, Shariah Court and other relevant agencies to preserve the rights of Muallaf in regard to their inheritance issues.